Pengaruh Pendapatan Asli Daerah terhadap Belanja Barang dan Jasa dengan Budget Ratcheting sebagai Variabel Moderating - Mariani Mariani; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to (a) determine the effect of Regional Original Income on goods and services expenditure (b) determine the Ratcheting budget in influencing the relationship of Regional Original Income with Goods and Services Expenditure. The population in this study is the APBD and LRA of the Regency/City Government of West Sumatra Province using the 2016-2019 time series obtained from djpk.kemenkeu.go.id. The data analysis technique used in this research is multiple regression analysis. From the results of this study, the value of t arithmetic < t table is 0.689 > 1.666 and a significant value of 0.448> 0.05, it can be explained that Regional Original Income does not affect the expenditure of goods and services. Then the test results on Budget Ratcheting decreased in Adjusted R Square from 42.4% in the first regression to 41.3% in the second regression. So it can be said that Budget Ratcheting weakens the relationship between Local Revenue and Expenditure on Goods and Services.